English Teaching in Vocational High School: A Need Analysis - Mahbub, Moh. Arif (JEELS (Journal of English Education and Linguistics Studies), 2018)
This research investigates the vocational school students’ needs on the implementation of English teaching and learning that is focused on the target needs and learning needs. By adapting Hutchinson and Waters’ model (1987), questionnaire consisting of parts A and B was administered to 32 students. Part A deals with the target needs centred on the learner’s necessities, lacks and wants that are effectively functioned in the target situation. In contrast, part B concerns about learning needs that encompass learning inputs, procedures, teacher’s and learners’ role, and setting. Additionally, interviews were also conducted with the students and an English teacher to gather data in order to examine in-depth results of the practices of English teaching and to uncover possible areas of students’ language difficulties in learning English. The results suggested that the students have different perceptions of their necessities, wants, and lacks. The findings also demonstrated the students’ learning needs including the learning inputs, teaching-learning procedures, the teacher’s and learners’ role, as well as the teachinglearning settings.